Real-Life Report on Chemoembolization Using DEBIRI for Liver Metastases from Colorectal Cancer. (26th February 2015) - Stutz, M.; Mamo, A.; Valenti, D.; Hausvater, A.; Cabrera, T.; Metrakos, P.; Chaudhury, P.; Steacy, G.; Garoufalis, E.; Kavan, P.
Abstract : Background . Transarterial chemoembolization (TACE) has been investigated in patients with liver metastases from colorectal cancer (LMCRC). Limited experience and available data suggest that TACE can achieve disease stabilization or improvement, even in heavily pretreated patients. Methods . Patients with LMCRC, ECOG 0–2, who failed at least 1 line of systemic chemotherapy, received embolizations with 2 mL of microspheres preloaded with 100 mg of irinotecan. Beads were delivered selectively into hepatic arteries. Primary endpoint was overall survival (OS), analyzed using the Kaplan-Meier method. Secondary endpoint was safety, assessed using CTCAE version 4.0. Results . 27 patients were treated using DEBIRI. Patient median age was 57 years (range was 45–82 years). The median number of total embolizations was 1.3 (range 1–3). The median OS was 5.4 months (95% CI; 1.1–22.7 months). The most reported postembolization events were nausea (8/27), vomiting (6/27), right upper quadrant pain (16/27), fatigue (9/27), and the development of ascites (6/27). 5/26 patients required hospitalization after TACE for severe pain. Hospitalization was also required for 1 case of allergic reaction and 1 case of infection. Conclusion . Our data suggest that TACE with DEBIRI could be efficacious in a palliative setting for patients with LMCRC, but they do not necessarily support routine use in clinical practice.